Integrating LFG’s binding theory with PCDRT - Dalrymple, M; Haug, D; Lowe, J (Institute of Computer Science, Polish Academy of Sciences, 2018)
We provide a formal model for the interaction of syntax and pragmatics in the interpretation of anaphoric binding constraints on personal and reflexive pronouns. We assume a dynamic semantics, where e-type expressions introduce discourse referents, and contexts are assignments of individuals to discourse referents. We adopt the Partial Compositional Discourse Representation Theory (PCDRT) of Haug (2014b),which models anaphoric resolution in terms of a pragmatically-established relation between discourse referents. We integrate PCDRT into the constraint-based grammatical framework of Lexical-Functional Grammar (LFG), and show how it is possible to state syntactic constraints on the pragmatic resolution of singular and plural anaphora within this framework.